Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Pemahaman Konsep Siswa Pada Materi Elastisitas Dan Hukum Hooke Di SMA Negeri 1 Syamtalira Bayu - Badriah, Badriah (Jurnal Dedikasi Pendidikan, 2022)
This study aims to determine the use of project-based learning models in improving students' conceptual understanding of elasticity and Hooke's law at SMA Negeri 1 Syamtalira Bayu. This research is a quasi-experimental design research. The sampling technique used is simple random sampling. The sample in this study were students of class XI IPA 4 . The design used in this study is the Nonequivalent Control Group Design. The research instrument was in the form of a concept understanding test. To test the hypothesis, the Independent sample test was used. Data analysis was done descriptively. The results of the research data analysis showed that the results of the normalized N-Gain obtained an average value of increasing understanding of the concepts of experimental class students, namely 0.46 in the medium category, while the control class was 0.30 in the low category. The results of the independent test analysis of the sample test for the experimental class and control class are 0.03 < 0.05, it can be concluded that the use of project based learning learning models can improve students' understanding of concepts on elasticity and Hooke's law at SMA Negeri 1 Syamtalira Bayu.